Evaluation of intrathecal baclofen delivery system malfunction by computed tomography scan. (11th September 2015) - Abousamra, Oussama; Rogers, Kenneth J; McManus, Maura; Miller, Freeman; Sees, Julieanne P
Abstract : Aim: To describe the computed tomography (CT) findings encountered when catheter patency is questionable. The role of CT in directing treatment is evaluated. Method: Records of children with intrathecal baclofen pump management were reviewed. Only patients with CT evaluation who had revision pump/catheter surgery were included. Results: From 295 patients, 27 had CT contrast study; in three of them, baclofen could not be aspirated and the procedure was stopped, eight had normal scan and did not need surgery and 16 patients were reported. Four patients had normal CT (free contrast formed a perfect crescent shape), and had surgery because the pump battery was close to expiration. Five patients had inadequate fluid pooling (fluid was seen without a crescent shape). Five patients had fluid leak (fluid was seen around the pump or in the lumbar canal below catheter entrance level or outside the canal in the lumbar region). Two patients had catheter occlusion (fluid loculation around the catheter tip with no free flow). Interpretation: CT contrast study is safe and effective for locating defects in intrathecal baclofen delivery system. When catheter patency is questionable, CT plays an important role in directing the next step of management. What this paper adds: Computed tomography (CT) contrast scan is a safe method in evaluating intrathecal baclofen delivery systems. CT is important in evaluating potential delivery problems with intrathecal pump catheter systems. This article is commented on by Farid on page329 of this issue.